Experimental and numerical studies of pin-ended S960 ultra-high strength steel press-braked channel section columns - Ong, Shao Quan (Nanyang Technological University, 2019)
Ultra-high strength steel (UHSS) Grade S960 with the nominal yield stress of 960 MPa, is receiving increasing attention due to its higher strength-to-weight ratio. However, its application in construction engineering is rather limited due to the lack of adequate design rules, as the current international standards established in Europe, America and Australia/New Zealand only cover the design of structural members with steel grades up to only S700. This has prompted extensive investigations on S960 UHSS structural members, and press-braked S960 UHSS plain channel section columns, for which there are currently no experimental data, are the focus of the present study. The flexural behaviour and strengths of the channel section columns were thoroughly examined through experimentation and numerical modelling, and fully reported in this paper. The structural testing programme were performed on two nonslender plain channel sections and comprised detailed measurements of initial global and local geometric imperfections, as well as a total of 10 flexural buckling tests on pin-ended columns buckling about their minor axes. A complementary numerical modelling programme was carried out to supplement the test data, and included a validation study to develop finite element (FE) models capable of replicating the test structural responses as well as a subsequent parametric study to utilise the validated FE models for generating further FE data over a wider spectrum of cross-section sizes and member lengths. The experimentally and numerically acquired data was used to evaluate the applicability of the codified column buckling design provisions and formulations to the design of pin-ended press-braked S960 UHSS plain channel section columns failing by minor-axis flexural buckling. The assessment results generally indicated that the current European code leads to overall conservative and scattered flexural buckling strength predictions for the examined plain channel section columns, while the American and Australian/New Zealand standards yield an overall higher level of accuracy and consistency, but with many over-predicted flexural buckling strengths for press-braked S960 UHSS plain channel section columns at intermediate slenderness range.